PLANNING FOR THE DEVELOPMENT OF CULTURAL TOURISM PRODUCTS ON THE NORTH COAST OF JAVA - Nugraha, Stevanus Christa; Marsongko, Eka Pramita; Suteja Wira Dana Kusuma (Politeknik Pariwisata NHI Bandung, 2023)
As one of the Chinese Traders, Cheng Ho’s Naval Route serves Cirebon, Semarang, and Surabaya to have a cultural identity that could be seen today. Now, the existence of cultural heritage that spread akong the Javanese Nort Coast serve tourist to learn about the cultural heritage that was shaped by Cheng Ho's Naval Route. On the other hand, the existence of this cultural heritage could be developed into alternative tourism that gives a new trend of tourism attraction yet supports cultural preservation. Through adopting the model of the Cultural Route that was advanced and developed in Europe, this research is titled “Planning of Cultural Tourism Product Development of Cheng Ho Naval Route along Javanese North Coast”. This research utilizes the qualitative approach and descriptive method as the analyzing method. The result of the research covers the Tourism Attraction and Activities aspect as a component of tourism products that attract tourists, Transportation Facilities and Services as a component that serves the movement of tourists, and Institutional Elements as an organization that manages the network of transboundary tourism attractions. The recommendation of Planning of Cultural Tourism Product Development of Cheng Ho Naval Route along the Javanese North Coast can be the reference for the stakeholders to invest in tourism development that supports the preservation of Cultural Heritage